2019
DOI: 10.1186/s42826-019-0024-y
|View full text |Cite
|
Sign up to set email alerts
|

Investigation of the effect of coffee on body weight, serum glucose, uric acid and lipid profile levels in male albino Wistar rats feeding on high-fructose diet

Abstract: Coffee is one of the most commonly consumed beverages in the worldwide and is assumed to have protective effects against metabolic syndrome. The present study was aimed at investigating the effect of coffee on body weight, serum glucose, uric acid and lipid profile levels in male albino Wistar rats feeding on high fructose diet. A post-test experimental study was conducted on a total of 30 (9-10 weeks old) male albino Wistar rats. The rats were divided into 6 groups: group I (normal control)-fed on standard ch… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
7
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 11 publications
(7 citation statements)
references
References 22 publications
0
7
0
Order By: Relevance
“…Various studies have proven the benefits of chlorogenic acid on blood glucose, such as delaying intestinal glucose absorption and inhibiting hepatic glucose output. Chlorogenic acid has a mechanism for reducing intracellular hyperglycemia and acts as a polyphenolic compound which works as a strong antioxidant in coffee (Yustisiani et al 2013;Feyisa et al 2019).…”
Section: Resultsmentioning
confidence: 99%
“…Various studies have proven the benefits of chlorogenic acid on blood glucose, such as delaying intestinal glucose absorption and inhibiting hepatic glucose output. Chlorogenic acid has a mechanism for reducing intracellular hyperglycemia and acts as a polyphenolic compound which works as a strong antioxidant in coffee (Yustisiani et al 2013;Feyisa et al 2019).…”
Section: Resultsmentioning
confidence: 99%
“…Regarding the lipid profile, there is no consensus concerning the effect of coffee [ 41 , 56 – 58 ]. In the present study, the consumption of FCS did not affect most lipid profile markers in the serum and liver, since the levels of cholesterol, TG, and LDL were similar between the control and high-fat diet groups, with and without the addition of FCS.…”
Section: Discussionmentioning
confidence: 99%
“…Similar to our results, Feyisa et al . [ 56 ] observed that rats fed coffee had higher HDL-C concentration than that in other rats. Some studies, most of which used purified compounds, showed that some polyphenols found in coffee (caffeic, ferulic, and phenolic acids) as well as in other foods stimulated reverse cholesterol transport by promoting HDL formation and cholesterol efflux [ 61 , 62 ].…”
Section: Discussionmentioning
confidence: 99%
“…No dose-dependent conclusion can be drawn from the changes observed in the 0.29 g/kg BW group, as the highest dose did not exacerbate the parameters measured. Contrarily, the consumption of coffee has been reported to decrease liver enzymes associated with liver damage and has shown protective effects attributed to its polyphenol content [ 38 , 39 , 40 , 41 , 42 , 43 ]. There were favorable significant reductions in liver enzymes (ALP and ALT) and lipid profile indicator (triglyceride) in the low male dose group but no trend was evident in the higher dose groups except in the female triglyceride level when given the high dose.…”
Section: Discussionmentioning
confidence: 99%